Geotourism: A perspective from Southwest Germany - Pforr, Christof; Megerle, A. (Butterworth Heinemann, 2006)
The aim of this chapter is to provide a brief overview of the development of geotourism in southwest Germany, focusing in particular on the Swabian Alb, which represents an ideal geotourism destination. In this context geotourism is understood as being more than just geological tourism (e.g. fossicking or visiting caves), and embraces the identification of geo-objects, landscape marketing and interpretation of the geological heritage of a region in a sustainable manner. Collaboration, coordination, effective communication and transfer of know-how are hereby discussed as important mechanisms to achieve sustainable outcomes. The Network History of the Earth (Netzwerk Erdgeschichte) is presented as a successful example of regional collaboration to promote sustainable geotourism.